Structural and mechanistic analysis of ATPase inhibitors targeting mycobacterial DNA gyrase. (30th July 2020) - Henderson, Sara R; Stevenson, Clare E M; Malone, Brandon; Zholnerovych, Yelyzaveta; Mitchenall, Lesley A; Pichowicz, Mark; McGarry, David H; Cooper, Ian R; Charrier, Cedric; Salisbury, Anne-Marie; Lawson, David M; Maxwell, Anthony
Abstract: Objectives: To evaluate the efficacy of two novel compounds against mycobacteria and determine the molecular basis of their action on DNA gyrase using structural and mechanistic approaches. Methods: Redx03863 and Redx04739 were tested in antibacterial assays, and also against their target, DNA gyrase, using DNA supercoiling and ATPase assays. X-ray crystallography was used to determine the structure of the gyrase B protein ATPase sub-domain from Mycobacterium smegmatis complexed with the aminocoumarin drug novobiocin, and structures of the same domain from Mycobacterium thermoresistibile complexed with novobiocin, and also with Redx03863. Results: Both compounds, Redx03863 and Redx04739, were active against selected Gram-positive and Gram-negative species, with Redx03863 being the more potent, and Redx04739 showing selectivity against M. smegmatis . Both compounds were potent inhibitors of the supercoiling and ATPase reactions of DNA gyrase, but did not appreciably affect the ATP-independent relaxation reaction. The structure of Redx03863 bound to the gyrase B protein ATPase sub-domain from M. thermoresistibile shows that it binds at a site adjacent to the ATP- and novobiocin-binding sites. We found that most of the mutations that we made in the Redx03863-binding pocket, based on the structure, rendered gyrase inactive. Conclusions: Redx03863 and Redx04739 inhibit gyrase by preventing the binding of ATP. The fact that the Redx03863-binding pocket is distinct from that of novobiocin, coupled with the lack of activity of resistant mutants, suggests that such compounds could have potential to be further exploited as antibiotics.